Review Of Ferry Transport Subsidies On The Padang – Siberut Pioneer Route in West Sumatera Province - Puspita Sari, Yulia; Ulya, Febriyanti Himmatul; Sesilia Putri, Salsabila Verandita; Mu'tamar, Rispa Saeful (IWJ : Inland Waterways Journal, 2025)
Teluk Bungus Ferry Port is a pioneer ferry port located in Bungus Teluk Kabung district, West Sumatera Province. This study aims to assess the effectiveness of subsidising ferry transport on the Padang-Siberut pioneer route served by KMP Ambu–Ambu. This research was conducted using a quantitative approach through the collection of primary and secondary data from relevant agencies, as well as using the ship operating cost analysis method and simple linear regression to project passenger and vehicle growth, ship operating costs and revenue from 2025 to 2030. The results of the study show that the average number of passengers and vehicles fluctuates, but shows a positive growth trend in 2025–2030. The Ship Operating Costs value in 2025 will reach Rp.10,355,532,711.02, with fixed costs, variable costs, overhead profit margin, and depreciation as the main factors. Meanwhile, revenue from ticket sales is not yet sufficient to cover the ship's operating costs. Based on the results of Ship Operating Costs forecasting and revenue in 2025–2030, the Break Even Point (BEP) of 26% indicates that the Padang–Siberut route is predicted to reach break-even point in March 2028, so that in 2028 it can be recommended to become a commercial route.